2016
DOI: 10.1515/enr-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Sympathectomized tumor-bearing mice survive longer but develop bigger melanomas

Abstract: Objectives.Previously we have shown that 20 days aft er the tumor cells injection smaller melanomas have been developed in chemically sympathectomized mice in comparison with animals having intact sympathetic nervous system. However, it is known that chemical sympathectomy reduces the sympathetic neurotransmission only temporarily. In the present study, we monitored the survival of the sympathectomized mice with melanoma with an attempt to fi nd out how long the suppressing eff ect of sympathectomy on the mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Using several experimental approaches (surgical as well as pharmacological), we have investigated the participation of sympathetic and parasympathetic nerves in cancer development and progression. Th e results obtained from our experimental studies have supported the stimulatory role of the sympathetic neurotransmission in the case of an intra-abdominal rat fi brosarcoma (Lackovicova et al 2011) and subcutaneous murine melanoma (Horvathova et al 2016b). However, the involvement of the parasympathetic nerves in growth of rat intra-abdominal fi brosarcoma has not been observed .…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Using several experimental approaches (surgical as well as pharmacological), we have investigated the participation of sympathetic and parasympathetic nerves in cancer development and progression. Th e results obtained from our experimental studies have supported the stimulatory role of the sympathetic neurotransmission in the case of an intra-abdominal rat fi brosarcoma (Lackovicova et al 2011) and subcutaneous murine melanoma (Horvathova et al 2016b). However, the involvement of the parasympathetic nerves in growth of rat intra-abdominal fi brosarcoma has not been observed .…”
Section: Discussionsupporting
confidence: 72%
“…In mice sacrifi ced in earlier stage of melanoma growth (on the 20 th day aft er B16-F10 melanoma cells injection), 6-OHDA treatment resulted in a signifi cant reduction of the tumor mass when compared to animals with the intact sympathetic nerves (Horvathova et al 2016a). Interestingly, in survival st udy we found that weight of the developed melanoma tissue in sympathectomized animals was signifi cantly increased in comparison with vehicle group animals (Horvathova et al 2016b).…”
Section: Interventions and Their Eff Ects On Tumor Growthmentioning
confidence: 78%
See 1 more Smart Citation
“…Regarding tumor progression, Horvathova et al [10,13] reported contradicting results on the effect of sympathectomy on tumor growth in a melanoma model. They found that sympathectomy delayed tumor development and significantly prolonged the survival of tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) was calculated at the end of the protocol as the product of dividing the corrected body weight between the square of the nose-anus length [9]. The general state of health of experimental animals was daily monitored, including known 6-OHDA side-effects such as ptosis (upper eyelid drooping) and presence of blood in urine [10].…”
Section: Mice Body Weight and Compositionmentioning
confidence: 99%